Green Circular Economy A New Paradigm for Sustainable Development - Singh, Pardeep; Yadav, Anamika; Chowdhury, Indranil; Singh, Ravindra Pratap (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book highlights the concepts, issues and policies related to the circular economy. The chapters of this book are designed to include the theoretical approach to the green circular economy, sustainable supply chain and challenges in the green circular economy. The book is a step towards designing sustainable circular economy embedded production and management practices. This book also addresses the capability of green-lean productions and a circular economy to improve resource efficiency and address environmental sustainability issues. Environmental sustainability is a hot topic in politics, science, and industry. There is a need to achieve economic, social, and environmental sustainability goals through adaptations of the green circular economy, which can help minimize greenhouse gas emissions, toxic pollutant releases, waste and energy and resource usage by employing renewable energy concepts and recyclable materials. The production processes must be resource-efficient and environmentally friendly, including green-lean manufacturing. Adopting a circular economy in manufacturing is less evident than green-lean management. However, systematic strategies to bridge this gap have yet to be devised. There is an urgent need to fully explore the Circular Economy concept to attain resource and environmental goals for the sustainability of the environment in the present era of global climate change. Its framework's powerful strategies need to solve the problem created by linear economic growth through industrialization and gross economic growth. There is a need to improve the sustainability management capabilities in the manufacturing and industrial sector to support the circular economy and a need to examine the impact of green human resource management. This book proposes the combined approach of green-lean solutions and a green circular economy. Through this book, we try to produce the content and information in a compiled form to give the audience an understanding of the circular economy concept framework and challenges.
Chapter 1. Circular economy aspirations: Three strategies in search of a direction -- Chapter 2. The environment value system and green circular economy -- Chapter 3. Circular economy and sustainable production and consumption -- Chapter 4. Green human resource management and circular economy -- Chapter 5. Economies of scale in green circular economies -- Chapter 6. Temporal study of the interrelationship between economics and environmental degradation -- Chapter 7. Cities as emerging centers in a circular economy: An assessment of Indian cities -- Chapter 8. Trade and management of waste -- Chapter 9. Carbon emission from liquid fuel and pollution haven hypothesis -- Chapter 10. The development practice and reform optimization path of green circular economy in Erhai Lake of China -- Chapter 11. Recent trends in biohydrogen economy: Challenges and future perspectives -- Chapter 12. Strategic planning and business sustainability in agribusiness: Analysis in a model farm in Brazil -- Chapter 13. Application of industrial ecology principles in and around cement industry in NCR of Delhi: Potentials, problems and possibilities -- Chapter 14. Challenges and recommendations for a green circular economy.
Keywords: Sustainability; Renewable energy sources; Power resources; Environmental economics; Economic development; Sustainability; Renewable Energy; Resource and Environmental Economics; Economic Growth